2007
DOI: 10.1074/jbc.m706039200
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of p53 Is Differentially Regulated by Brm- and Brg1-containing SWI/SNF Chromatin Remodeling Complexes

Abstract: Brahma (Brm) and Brahma-related gene-1 (Brg1) ATPases share similarities in structure and function, but their presence in human SWI/SNF chromatin remodeling complexes is mutually exclusive. Although Brm and Brg1 can compensate for each other, it is possible that Brm and Brg1 have their unique properties to differentially regulate gene expression in vivo. To explore this, we examined the requirement of Brm and Brg1 for p53-dependent transcription, especially p53-mediated induction of p21 and MDM2, using cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
56
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 34 publications
5
56
0
1
Order By: Relevance
“…Nevertheless, our and other studies also suggest an existence of p53-independent mechanism(s) in tumor suppression. RNAi technology has allowed the search for novel tumor suppressors using a genetically defined tumorigenic system (43,44), leading to the discovery of chromatin-modifying factors, including BRD7, TIP60, and HDAC4 (5,9,43). Similar to our findings on hTOP3a, these enzymes either serve as cofactors of p53 on tumor suppression or are required for its optimal transcriptional activity.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Nevertheless, our and other studies also suggest an existence of p53-independent mechanism(s) in tumor suppression. RNAi technology has allowed the search for novel tumor suppressors using a genetically defined tumorigenic system (43,44), leading to the discovery of chromatin-modifying factors, including BRD7, TIP60, and HDAC4 (5,9,43). Similar to our findings on hTOP3a, these enzymes either serve as cofactors of p53 on tumor suppression or are required for its optimal transcriptional activity.…”
Section: Discussionsupporting
confidence: 72%
“…Through the interactions with p53, chromatin factors modulate p53 expression and p53-mediated tumor suppression (5,8,9). Here, we have identified the topology-resolving hTOP3a protein as a candidate anticancer block in p53-mediated tumor suppression.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A previous study showed that the specifying component exclusive to the PBAF complex, BAF180 (polybromo-1), physically binds the p21 promoter (10). This observation was also made regarding BRG1, which functions interchangeably with structurally related BRM1 as one of the two SWI/SNF ATPase subunits in BAF complexes, although it is the only ATPase subunit used by the PBAF complex (11,12). Here, we show that BRD7 is a critical mediator of the ability of p53 to transduce the replicative and oncogene-induced senescence signal to p21 to initiate the senescence program of differentiation.…”
mentioning
confidence: 90%
“…Distinct functions for BRM-and BRG-based complexes have been observed in smooth muscle development, 15 osteoblast differentiation, 16 as well as cellular proliferation. 14,[17][18][19][20][21][22] BRM depletion is essential for neoplastic transformation of mouse fibroblasts by various oncogenes and its overexpression is sufficient to revert the RasV12 transformed phenotype. 17 In contrast to BRM, BRG is essential for oncogenic transformation of mouse fibroblasts and tumor formation in BAF47 null mice.…”
Section: Introductionmentioning
confidence: 99%